Biodiesel production from leather industry wastes - Luís Ramos (2008)
Animal fat was extracted from fleshings, a residue from the leather industry, by a two step procedure. First the fleshings are mixed with water (60 ºC) and then the fat rich phase obtained is treated with n-hexane to extract the fat and leave the proteic residue. This fat presents a high acid value and therefore the direct transesterification to biodiesel with an alkaline catalyst was not possible. A pre-treatment step was performed, consisting of an esterification reaction with methanol in the presence of sulfuric acid, and acid values were lowered below 3 mg KOH/g. The transesterification with methanol was carried out with KOH as catalyst at 65ºC in two stages using 80% of the methanol/KOH solution in the first step and the remaining in the second step. The methyl ester product was characterized and the parameters are, in most cases, within the specifications. The exception is the methyl ester content (94,2%) indicating that further adjustments are needed in the production process in order to improve the quality of the final product.